2015
DOI: 10.3390/w7031030
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotopic Analysis on Water Utilization of Two Xerophytic Shrubs in a Revegetated Desert Area: Tengger Desert, China

Abstract: Stable isotope studies on stable isotope ratios of hydrogen and oxygen in water within plants provide new information on water sources and water use patterns under natural conditions. In this study, the sources of water uptake for two typical xerophytic shrubs, Caragana korshinskii and Artemisia ordosica, were determined at four different-aged revegetated sites (1956, 1964, 1981, and 1987) in the Tengger Desert, a revegetated desert area in China. Samples from precipitation, soil water at different soil layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
0
20
1
Order By: Relevance
“…This result is in accordance with the suggestion by Li et al (2007) that at our study site the water content of the topsoil does not change with increasing age of C. korshinskii while that of the deeper soil layer decreases significantly with increasing age of the shrub. In the Shapotou area, rainfall is mainly characterized as a small rainfall pulse, with rain events of 0-10 mm precipitation accounting for 76 % of the total precipitation (Huang and Zhang 2015). In our study, ten small rain events accounted for the 57.9 mm of rain which fell during July (data not shown).…”
Section: Relationships Among Gas Exchange Plant Water Potential and mentioning
confidence: 42%
See 1 more Smart Citation
“…This result is in accordance with the suggestion by Li et al (2007) that at our study site the water content of the topsoil does not change with increasing age of C. korshinskii while that of the deeper soil layer decreases significantly with increasing age of the shrub. In the Shapotou area, rainfall is mainly characterized as a small rainfall pulse, with rain events of 0-10 mm precipitation accounting for 76 % of the total precipitation (Huang and Zhang 2015). In our study, ten small rain events accounted for the 57.9 mm of rain which fell during July (data not shown).…”
Section: Relationships Among Gas Exchange Plant Water Potential and mentioning
confidence: 42%
“…Our results showed that A, g s and W had a close relationship with SWC (soil depth 0-40 cm), RH and VPD-but no relationship with SWC (soil depth 40-80 cm)-suggesting that the photosynthetic activity and water potential of C. korshinskii shrubs were affected by both soil and atmospheric water availability, but not by the water content in the deeper soil layers. It is therefore possible that during the growing season in the Shapotou area, the main source of water tapped by C. korshinskii was that available in the upper soil layers (Huang and Zhang 2015).…”
Section: Influence Of Environmental Factors On Photosynthesis and Plamentioning
confidence: 99%
“…Water in stem and soil samples were extracted by the cryogenic vacuum distillation system (LI-2000, LICA, Beijing, China) ( Figure 1f). The Los Gatos Research (LGR) DLT-100 liquid water isotope analyzer (Mountain View, CA, USA) was used to measure the isotope composition of 18 the VSMOW international standards and then converted to δD and δ 18 O values. The precision for δD and δ 18 O measurements was ±1‰ and ±0.1‰, respectively.…”
Section: Water Sample Collections and Isotope Analysesmentioning
confidence: 99%
“…The MixSIAR model incorporates advances in MixSIR and SIAR that considers multiple sources of uncertainty and provides potential proportions of source contributions [12]. The MixSIAR model has been employed successfully to determine the contributions of soil water at different layers to the water uptake of field crops and natural plants [13][14][15].Using water stable isotopes to determine plant water sources has gained significantly more attention in relation to forest, grass, and shrub ecosystems in the past three decades [16][17][18]. Only 15% of previous studies tracked RWU in agricultural systems (e.g., maize, wheat, millet, rice, and alpine crops) [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation